Glutaredoxin-2 Controls Mitochondrial Structure and Energetics in Skeletal Muscle - Liaghati, Awa (Université d'Ottawa / University of Ottawa, 2017)
Glutathione (GSH) plays a pivotal role in cellular redox poise, which is disordered in many metabolic diseases including type 2 diabetes. Glutaredoxin-2 (Grx2) is a glutathione transferase in mitochondria and the nucleus. We previously established that Grx2 knockout (Grx2-/-) mice have low GSH:GSSG and mitochondrial dysfunction in isolated mitochondria of muscle and heart. Moreover, low GSH:GSSG stimulates mitochondrial fusion in transformed cell lines. Our goal was to study the impact of Grx2-/- on the GSH ratio and on mitochondrial structure and function in situ and in intact primary muscle cells. Compared to wild-type (WT), Grx2-/- myoblasts have a decreased GSH:GSSG, with a marked increase in mitochondrial length. Mitochondrial ultrastructure is profoundly abnormal in the Grx2-/- muscle compared to WT. Furthermore, mitochondrial content is significantly reduced in the Grx2-/- muscle. Mitochondrial energetic analyses in myofiber preparations confirm impaired CI activity and reveal impaired fatty acid oxidation capacity. In summary, the absence of Grx2 causes marked abnormalities in mitochondrial ultrastructure in skeletal muscle and in cellular GSH redox state and mitochondrial length.
Keywords: Mitochondrial dynamics; Glutathione redox; Skeletal muscle